2017
DOI: 10.1111/adj.12522
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and curriculum design: a global survey in dental education

Abstract: This survey indicated considerable variation in curriculum structure with regionally-specific preferences being evident in terms of curriculum structure, teaching philosophies and motivation for incorporation of VR haptic simulation into curricula. This study illustrates the need for an improved evidence base on dental simulations to inform curriculum designs and psychomotor skill learning in dentistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
3
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 51 publications
0
31
3
4
Order By: Relevance
“…Cariology includes research in dental hard tissues, dental wear (erosive/ non-erosive), and dental hard tissue disorders [13]. This wider view of cariology opens new perspectives in dental education and research, being a strong motive for improving diagnostic skills, while treating and preventing carious lesions in more effective ways [15,16].…”
Section: Principles Of Cariology: Dental Caries Reviewedmentioning
confidence: 99%
“…Cariology includes research in dental hard tissues, dental wear (erosive/ non-erosive), and dental hard tissue disorders [13]. This wider view of cariology opens new perspectives in dental education and research, being a strong motive for improving diagnostic skills, while treating and preventing carious lesions in more effective ways [15,16].…”
Section: Principles Of Cariology: Dental Caries Reviewedmentioning
confidence: 99%
“…A literature review of 3D technologies in anatomical education showed that a majority of studies reported positive outcomes but none reported negative impacts on cognitive loads of users (Hackett and Proctor, ). Particularly, the development of 3D simulators coupled with augmented reality, automated feedback, and /or haptic response for surgical procedures has proven useful in skills development and consolidation while providing standardization of execution amongst students (Bakr et al, ; Perry et al, ; Roy et al, ; Kwon et al, ). Moreover, augmented reality was recently introduced to teach dental procedures such as cavity preparation, showing favorable response from dental students (Llena et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Funda Akaltan(0000-0001-6744-6312)  Selcuk Dent J, Diş Hekimliği Eğitimini Yeniden Düşünmek -Özel Sayı (Doi: 10.15311/selcukdentj.563351) Diş hekimliği günümüz müfredatı; geleneksel, entegre veya bunların karışımı şeklindeki felsefeyi uygulayarak, tasarım stili açısından farklılık göstermektedir. 1 "Geleneksel müfredat"; preklinik temel bilimler ile sonraki senelerde uygulamalı eğitimle birlikte klinik deneyim kazandırır. Dersleri esas alır ve önceden tanımlanmış, disipline dayalı eğitimde, konuların biraraya getirilerek anlaşılmasını zorlaştırır.…”
Section: Diş Hekimliğinde Preklinik Ve Klinik Eğitim çEşitliliğiunclassified
“…26,27 Diş hekimliğinde simülasyon eğitimi; öğrenci için güvenli uygulama yapma ve işlemsel becerilerini, hastalar üzerinde uygulama yapmadan önce belirlenen standartlara/yeterliklere ve öğrenim çıktılarına göre geliştirme imkanı bulmaları açısından önemli bir çekirdek müfredat bileşenidir. 1 Klinik uygulama için gereken farklı tekniklerin öğrenimindeki simülasyon uygulamaları; geleneksel olarak doğal veya sentetik dişler içeren fantom kafalarda yapılır. Sanal gerçekliğin dental müfredat içindeki uygulamalarının artması; işlemleri tekrarlama ve standardize etme kolaylığı ile öğrencilerde doğrudan gözlem yapma ve malzeme sarfını azaltmak için tercih edilir.…”
unclassified